Internal Information Quality’s Role in Tax Avoidance and Earnings Disclosure Transparency - Indah Masri; Amelia Oktrivina; Tryas Chasbiandani (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This research investigates how Internal Information Quality (IIQ) moderates the link between aggressive tax avoidance and earnings disclosure transparency in consumer goods manufacturing firms from 2022 to 2024. Employing a quantitative method with financial statement data, the study finds that aggressive tax strategies significantly raise discretionary revenue, reducing transparency. IIQ acts as a moderating factor, where delays in financial reporting suggest potential earnings manipulation aimed at presenting a favourable image to stakeholders. Such delays may reduce the informative value of disclosures. The findings highlight the need for stronger corporate governance and the adoption of real-time financial reporting systems to minimise information asymmetry. This study enhances tax accounting literature by showing that IIQ impacts operational decisions and influences the reliability of financial disclosures.